A validation study of DNA methylation-based age prediction using semen in forensic casework samples. (March 2018) - Lee, Jee Won; Choung, Chong Min; Jung, Ju Yeon; Lee, Hwan Young; Lim, Si-Keun
Highlights: A validation study of a previously published age-predictive method was conducted. Concordance testing showed a high correlation between the predicted and real age. The method produced reproducible results with >5 ng of bisulfite-converted DNA. Applicability of the method in forensic casework was confirmed. Abstract: Previously, an age-predictive method based on DNA-methylation patterns in semen was developed, using three CpG sites (cg06304190 in the TTC7B gene, cg12837463, and cg06979108 in the NOX4 gene). Before considering the routine use of a new method in forensics, validation studies such as concordance and sensitivity tests are essential for obtaining expanded and more reliable forensic information. Here, we evaluated a previously described age-predictive method for semen for routine forensic use. Concordance testing showed a high correlation between the predicted and chronological age, with a mean absolute deviation from the chronological age of 4.8 years. Sensitivity testing suggested that age prediction with reliable accuracy and consistency was possible with >5 ng of bisulfite-converted DNA. We also confirmed the applicability of the age-predictive method in forensic casework, using forensic samples. Thus, the proposed method could serve as a very valuable forensics tool for accurate age prediction with semen samples.